2018
DOI: 10.1080/17482631.2018.1503909
|View full text |Cite
|
Sign up to set email alerts
|

Feeling happy and carefree: a qualitative study on the experiences of parents, medical clowns and healthcare professionals with medical clowns

Abstract: Purpose: To explore the effect of medical clowns and its relevant actors and conditions. Method: Semi-structured interviews were conducted with fourteen parents who had experiences with medical clowns in the Netherlands. Four focus groups were held with seven medical clowns and 25 healthcare professionals. The interviews and focus groups were audio-recorded and transcribed verbatim. Content analysis was used to analyse the data. Results: Concerning the clown effect, we distinguished the following themes: happi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Studies which showed that medical clowning also has a positive impact on adults were conducted among children's parents, caregivers and medical staf [57,58], women undergoing IVF treatment for pregnancy [59], and patients coping with psychiatric disorders [60]. However, there is little research on medical clowning with older adults residing in specialized institutions, such as residential care facilities, assisted living facilities, and nursing homes [61,62].…”
Section: Medical Clowningmentioning
confidence: 99%
“…Studies which showed that medical clowning also has a positive impact on adults were conducted among children's parents, caregivers and medical staf [57,58], women undergoing IVF treatment for pregnancy [59], and patients coping with psychiatric disorders [60]. However, there is little research on medical clowning with older adults residing in specialized institutions, such as residential care facilities, assisted living facilities, and nursing homes [61,62].…”
Section: Medical Clowningmentioning
confidence: 99%
“…Distress and anxiety are widespread in children undergoing medical procedures [ 7 ]. MC interventions may distract children from pain-inducing sources, which may reduce psychological distress and pain in these children and their parents, in addition to increasing their cooperation during medical procedures [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%